2017
DOI: 10.2217/bmm-2017-0090
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of PlncRNA-1 and TUG1 : Potential Biomarkers for Gastric Cancer Diagnosis and Clinically Monitoring Cancer Progression

Abstract: In conclusion, PlncRNA-1 and TUG1 genes may play a critical role in GC progression and may serve as potential diagnostic biomarkers in GC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…A research group found that FAM83H-AS1 was a crucial lncRNA expressed at preliminary stage of breast cancer by RNA sequencing in early-stage tumors, suggesting detection of FAM83H-AS1 expression levels in plasma could be a potential diagnostic and prognostic biomarker for early-stage of breast cancer [33]. However, in contrast to other reports, Baratieh's study showed that upregulated expression of FAM83H-AS1 in kidney renal papillary cell carcinoma led to longer survival rates [14]. Chemotherapy is one of the most effective methods to treat tumors and is the main treatment for some tumors that have the tendency of metastasis and those that have already metastasized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A research group found that FAM83H-AS1 was a crucial lncRNA expressed at preliminary stage of breast cancer by RNA sequencing in early-stage tumors, suggesting detection of FAM83H-AS1 expression levels in plasma could be a potential diagnostic and prognostic biomarker for early-stage of breast cancer [33]. However, in contrast to other reports, Baratieh's study showed that upregulated expression of FAM83H-AS1 in kidney renal papillary cell carcinoma led to longer survival rates [14]. Chemotherapy is one of the most effective methods to treat tumors and is the main treatment for some tumors that have the tendency of metastasis and those that have already metastasized.…”
Section: Discussionmentioning
confidence: 99%
“…The 14 studies contained 2818 patients from three countries including China, United States and Iran. We mainly analyzed nine different types of tumors, including pancreatic ductal adenocarcinoma [13], gastric cancer [7,14,15], ovarian cancer [8,16], glioma [9], colorectal carcinoma [17,18], bladder cancer [10], hepatocellular carcinoma [6], breast cancer [19], and lung cancer [20]. The expression of FAM83H-AS1 was detected by quantitative real-time fluorescent PCR in all studies.…”
Section: Characteristics and Basic Information In Eligible Literaturementioning
confidence: 99%
“…It has been revealed that there were significant higher levels of PlncRNA-1 and TUG1 expressions in a sub population of Iranian GC tissues compared with normal margins. The PlncRNA-1 expression level was correlated with sex in which female patients had a significantly PlncRNA-1 over expression compared with males [97]. PlncRNA-1 expression level was significantly over expressed in Chinese HCC tissues that was significantly associated with tumor size and advanced TNM stage [98].…”
Section: Gastric Cancermentioning
confidence: 95%
“…PlncRNA-1 is encoded from the antisense strand of the carbonyl reductase 3 (CBR3) on chromosome 21q. PlncRNA-1 is over expressed in various cancers including PCa, ESCC, and hepatocellular carcinoma (HCC) [97]. It has been revealed that there were significant higher levels of PlncRNA-1 and TUG1 expressions in a sub population of Iranian GC tissues compared with normal margins.…”
Section: Gastric Cancermentioning
confidence: 99%
“…A total of 30 pairs of gastric cancer and matched adjacent nontumoral tissues were obtained from patients with gastric cancer. The specimens were collected by the Iran National Tumor Bank, which is funded by the Cancer Institute of Tehran University, for Cancer Research (19)(20)(21). There, the tissues are immediately snap-frozen in the liquid nitrogen.…”
Section: Clinical Specimensmentioning
confidence: 99%